The Impact of Social Media Marketing Towards Purchase Intention Sequentially Mediated by Brand Equity and E-WOM: A Case of Erigo - Allen Widhi Wiratama; Nicola Nicola (iBuss Management, 2023)
Nowadays, in the digital business world, social media marketing is a very crucial aspect of marketing that a company should use. Brands should know how to engage customers’ purchase intentions through social media marketing. As one of the most popular clothing brands in Indonesia, Erigo shows a great social media marketing in Instagram. However, whether the impact of social media marketing can be translated directly or indirectly to purchase intention is still unknown. This research will examine whether social media marketing significantly influences purchase intention directly or social media marketing significantly influences purchase intention through the mediation of brand equity and e-WOM. The data were gathered by utilizing the simple random sampling technique. Online questionnaires were spread to collect the data. The data was analyzed using Smart-PLS. Result shows that social media marketing has a significant impact on purchase intention, social media marketing has a significant impact on brand equity, brand equity has a significant impact on e-WOM, e-WOM has a significant impact on purchase intention. Moreover, social media marketing has more significant effect towards purchase intention when mediated through brand equity and e-WOM. Furthermore, limitations and future directions are shown in the end.  Keywords: Social media marketing, Brand equity, Electronic word of mouth, Purchase intention, Instagram, Erigo, Indonesia.